SMART SAVING: MENGUBAH KEBIASAAN KECIL MENJADI KEBEBASAN FINANSIAL - Daffa Ahmad Athalla; Hilda Khoirunnisa; Nazwa Safitri (LAP4B, 2026)
Financial literacy is a fundamental competency that should be introduced from an early age to develop responsible financial behavior, particularly given the persistently low levels of financial literacy among Indonesian children relative to developed countries and the OECD average. Limited understanding among children regarding the importance of saving and managing pocket money may hinder the formation of positive financial habits in the future, a concern that is also reflected in international assessments of students' financial literacy. Therefore, this Community Service Program (PKM) implemented the